“Enhancing Creativity and Cultural Identity in Children through Folk Applied Arts” - Raxmonova Rayxon Zoir qizi (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
Abstract: This article examines the role of folk applied arts in promoting creativity, aesthetic development, and cultural identity in school-age children. Hands-on activities such as designing traditional patterns, crafting ornaments, and experimenting with colors and textures help children develop fine motor skills, visual perception, problem-solving abilities, and critical thinking. Incorporating folk arts into educational programs fosters cultural literacy, social interaction, and creative expression, offering a comprehensive approach to holistic child development.